Diabetes, Obesity, and Breast Cancer - Kang, Chifei (Endocrinology, 2018)
The rates of obesity and diabetes are increasing worldwide, whereas the age of onset for both obesity and diabetes are decreasing steadily. Obesity and diabetes are associated with multiple factors that contribute to the increased risk of a number of different cancers, including breast cancer. These factors are hyperinsulinemia, elevated IGFs, hyperglycemia, dyslipidemia, adipokines, inflammatory cytokines, and the gut microbiome. In this review, we discuss the current understanding of the complex signaling pathways underlying these multiple factors involved in the obesity/diabetes–breast cancer link, with a focus particularly on the roles of the insulin/IGF system and dyslipidemia in preclinical breast cancer models. We review some of the therapeutic strategies to target these metabolic derangements in cancer. Future research directions and potential therapeutic strategies are also discussed.